Photoselective shade nets reducing postharvest decay development in pepper fruits - A. Goren; S. Alkalia-Tuvia; Y. Perzelan; Z. Aharon; E. Fallik (Advances in Horticultural Science, 2013)
During two-year studies, we evaluated the influence of photoselective coloured shade nets on the quality of fresh harvested pepper fruits (Capsicum annuum) after prolonged storage and shelf life simulation. Pepper cultivar ‘Romans’ grown in a semi arid region under 35% pearl and yellow shade nets significantly maintained better pepper fruit quality after 16 days at 7°C plus three days at 20°C, mainly by reducing decay incidence during two consecutive years (2008 and 2009), compared to commercial black and red nets. No significant differences were observed in percentage of weight loss, firmness and total soluble solids in fruit harvested under the different coloured shade nets. The skin colour of fruit harvested under Pearl net was significantly lighter than that of fruit harvested under red and black shade nets and this fact can be associated with inhibition of fruit ripening during growth. After storability and shelf life simulation however skin colour was red to dark red under all shade nets. Pearl and yellow shade nets significantly reduced Alternaria spp. population in the field, which was evaluated with Alternaria-selective growing medium. The highest Alternaria population was found under red shade net. The significant low decay incidence in fruit harvested under pearl and yellow shade nets can be explained by the low inoculum level of Alternaria spp. in the field, and inhibition of fungal sporulation, and/or by a slowing of fruit ripening during its growth, reducing fruit susceptibility to fungal infection in the field due to the scattered light, its quality and the ratio between the light spectrum under the two shade nets.